The Impact of CSR on Consumers’ purchase intention in Chinese e-commerce companies - Wang, Manxi (2020)
Corporate Social Responsibility (CSR) refers to the commitment and responsibility of companies to reduce harmful effects and to have a positive impact on society and the environment. It has become mainstream as an increasing number of companies adopt this practice. There has been extensive research on the impact of CSR on a company's financial performance. However, relatively little research has been conducted on the impact of CSR on consumer behavior, particularly in developing or emerging markets. China's e-commerce enterprises as the emerging industries have developed rapidly in recent years. To fill the research gap in China, this study utilized qualitative research methods and in-depth semi-structured interviews to explore the impact of CSR on consumer purchase behavior in China's e-commerce industry, as well as consumer perception and behaviors towards CSR, purchase decision-making factors, and the willingness to pay a premium for CSR. The results show that CSR can affect consumers' purchasing decisions, and consumers are willing to pay a premium to support CSR practices when they have CSR perception. Moreover, consumers' awareness and perception towards CSR can affect their attitude toward it, if consumers have enough truthful CSR information, the company's ethical operations can have a positive impact on their response to CSR activities. However, without enough information, CSR may not have an impact on consumer behavior. The results of this paper will provide some useful suggestions for the management of enterprises.